Concise Review: Resistance to Tyrosine Kinase Inhibitors in Non-Small Cell Lung Cancer: The Role of Cancer Stem Cells. (5th February 2018) - Del Re, Marzia; Arrigoni, Elena; Restante, Giuliana; Passaro, Antonio; Rofi, Eleonora; Crucitta, Stefania; De Marinis, Filippo; Di Paolo, Antonello; Danesi, Romano
Abstract : Among the potential mechanisms involved in resistance to tyrosine kinase inhibitors (TKIs) in non-small cell lung cancer, the manifestation of stem-like properties in cancer cells seems to have a crucial role. Alterations involved in the development of TKI resistance may be acquired in a very early phase of tumorigenesis, supporting the hypothesis that these aberrations may be present in cancer stem cells (CSCs). In this regard, the characterization of tumor subclones in the initial phase and the identification of the CSCs may be helpful in planning a specific treatment to target selected biomarkers, suppress tumor growth, and prevent drug resistance. The aim of this review is to elucidate the role of CSCs in the development of resistance to TKIs and its implication for the management of patients. Abstract : Among the potential mechanisms involved in resistance to tyrosine kinase inhibitors (TKIs) in non-small cell lung cancer (NSCLC), the manifestation of stem-like properties in cancer cells seems to have a crucial role. Mechanisms of resistance may include appearance of stem-like properties by the over-expression of CSC antigens or increased expression of ALDH and ABC transporters (SP+ cells); de-regulation of signal transduction pathways (i.e., Notch, Wnt/β-catenin, and Hedgehog); acquisition of genetic ( EGFR and KRAS mutations, ALK translocation) and epigenetic (i.e., miRNA) alterations. In this regard, the characterization of tumor subclones at initial phase and the identification of the CSCs may be more effective in planning a specific treatment targeting specific biomarkers, suppressing tumor growth, and preventing drug resistance.